BT-09 Anhidrosis in neurohypophyseal germinoma treated with CBDCA and VP-16 - Adachi, Koji (Neurooncol Adv, 2020)
Introduction: Acquired generalized anhidrosis (AGA) is the disease with non-congenital, non-segmented diffuse sweating dysfunction and is associated with neurological signs and dysautonomia except for anhidrosis. Here we have experienced 2 cases of AGA in the patient with neurohypophyseal germinoma after carboplatin (CBDCA) plus etoposide (VP-16) (CARE) therapy. Relationship of AGA to neurohypophyseal germinomas and their treatment is discussed. Cases: We experienced two young (26 y/o and 27 y/o) female neurohypophyseal germinoma cases of anhidrosis. They received CARE as chemotherapy and whole ventricular irradiation. They showed heat retention 2 to 3 years after initial treatment without recurred germinoma. Because acetylcholine sweating test was negative and skin biopsy revealed normal sweat gland structure, the diagnosis of acquired idiopathic generalized anhidrosis (AIGA), idiopathic pure sudomotor failure subtype, was initially made. After steroid pulse therapy, sweat function recovered partially and completely. Discussion: AIGA and germinoma are both rare diseases. So, the present 2 cases have similar clinical settings, that anhidrosis may not be idiopathic but secondary. Affected responsible site of anhidrosis in the present cases is thought to be acetylcholine receptor in the sweat cells. The present cases did not have any known disease with anhidrosis and did not receive any medication which cause anhidrosis written in the statement of the virtues of a medicine. Commonly used drugs in both cases are infusion solutions, CARE and related drugs, hormone stimulating test agents. Recently anhidrosis is reported in a case of cancer of unknown primary tumor site after using CBDCA and PTX. Both of the present cases are used CBDCA, which may cause anhidrosis. Conclusion: CBDCA may attributed to the occurrence of AGA based on hypothalamic vulnerability.